2006
DOI: 10.1080/09553000600577821
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle arrest and apoptosis inCaenorhabditis elegansgermline cells following heavy-ion microbeam irradiation

Abstract: These results indicate that the microbeam irradiation is useful in characterizing tissue-specific, local biological response to radiation in organisms. DNA damage-induced cell cycle arrest and apoptosis were observed in locally irradiated regions, but there was little, if any, 'bystander effect' in the nematode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 19 publications
2
38
1
Order By: Relevance
“…These results show that similar egg-lethal effects of high energy carbon ions occur before and after hatching, and that high-LET radiation does not additionally induce lethal effects on eggs in the body of C. elegans. This may support the hypothesis that the bystander effect is little if any in the last stage of embryogenesis of germ-line in C. elegans (Sugimoto et al, 2006), although the bystander-induced expression of heat-shock protein HSP-4 was reported (Bertucci et al, 2009). Taken together, we found that eggs of C. elegans were more sensitive to high-LET radiation exposure than to low-LET radiation exposure.…”
Section: Dose Response For Hatchabilitysupporting
confidence: 78%
See 2 more Smart Citations
“…These results show that similar egg-lethal effects of high energy carbon ions occur before and after hatching, and that high-LET radiation does not additionally induce lethal effects on eggs in the body of C. elegans. This may support the hypothesis that the bystander effect is little if any in the last stage of embryogenesis of germ-line in C. elegans (Sugimoto et al, 2006), although the bystander-induced expression of heat-shock protein HSP-4 was reported (Bertucci et al, 2009). Taken together, we found that eggs of C. elegans were more sensitive to high-LET radiation exposure than to low-LET radiation exposure.…”
Section: Dose Response For Hatchabilitysupporting
confidence: 78%
“…− 9 − findings imply that DNA damage induced by high-LET radiation underlie high RBE for hatchability in C. elegans. The hatchability observed in this study is very close to its previously reported values in eggs laid from 0 -4 h following the whole-body high-LET irradiation of young adult C. elegans (Sugimoto et al, 2006). These results show that similar egg-lethal effects of high energy carbon ions occur before and after hatching, and that high-LET radiation does not additionally induce lethal effects on eggs in the body of C. elegans.…”
Section: Dose Response For Hatchabilitysupporting
confidence: 76%
See 1 more Smart Citation
“…(20) Targeted heavy-ion irradiation to only a very small fraction of cells within the whole cell population was carried out using microbeams installed at the Takasaki Ion Accelerator for Advanced Radiation Application of Japan Atomic Energy Agency, for which the set-up and irradiation procedures have been described. (10,18,(21)(22)(23)(24)(25) By using microbeams collimated through a 20-μm-diameter aperture, each of 1, 5, or 25 cells within the whole population was targeted with the precise number of carbon ions (18.3 MeV/u, LET = 103 keV/μm), as described previously. (10,18,25) In a dish, 1.3 × 10 6 ± 0.4 × 10 6 cells were populated in confluent cultures that were then irradiated, and then the fraction of hit cells among the whole population was estimated to be 0.0001, 0.0004, and 0.002% when 1, 5, and 25 cells were targeted.…”
Section: Methodsmentioning
confidence: 99%
“…1) was immersed in 70% ethanol bath for 1 h, exposed to UVC light for 3 h, and then used for cell inoculation. Considering that roughly 80% of the particle fluence collimated through a 20-µm-diameter microaperture was confined to the area of central 20-µm circle around which the remaining 20% was scattered to the area of 15-µm-wide annulus (Sugimoto et al, 2006), we refer to the unit of the target number herein as the site, rather than the cell. For all the experiments, 10 particles of three different types of heavy ions (physical properties listed in Table 1) were delivered to each of 1, 5 and 25 sites with a matrix distribution of 3 mm x 3 mm area in the center of the dish .…”
Section: Heavy-ion Irradiationmentioning
confidence: 99%